MU’ASYARAH BIL MA’RUF SEBAGAI ASAS PERKAWINAN - Hilmi, Ismi Lathifatul (Fakultas Agama Islam UNISMA, 2023)
Today the public is made aware of domestic problems through social media or through interactions with neighbors. Fulfilling each other's rights and responsibilities in the household is very important. The term mu'asyarah bil ma'ruf is used to describe this whole privilege and responsibility. The purpose of this study is to provide an explanation of the Islamic principle of marriage known as mu'asyarah bil ma'ruf, which requires a series of responsibilities and privileges for each family unit. This article takes an approach based on the Qur'an and Hadith by mentioning a number of postulates about mu'asyarah bil ma'ruf. This research resulted in a point of view of understanding drawn from the Qur'an and hadith through its interpretation of mu'asyarah bil ma'ruf where mu'asyarah bil ma'ruf is a concept of interdependence between husband and wife to present every good deed in the household when interacting and good communication between the two.